Redesain User Interface Pada Website Arlang Tour and Travel Menggunakan Metode User Centered Design Sebagai Media Promosi - Indahyani, Ilma dwi; Haq, Endi Sailul; Hakim, Lukman (Jurnal Informatika dan Komputer, 2024)
The development of information technology in Indonesia, particularly in the tourism sector, has experienced rapid progress. Tourism in Indonesia has become one of the main pillars in supporting national economic growth. CV. Arlang Tour and Travel, a travel agency, has also contributed to this sector. However, their website is still not optimal in terms of attractiveness and completeness of information. The initial survey results, conducted using the System Usability Scale, showed an average score of 52 from 30 respondents, with a grade scale of D, indicating that the website's usability is still below average. This research aims to evaluate and redesign the website, focusing on enhancing content completeness using the User Centered Design (UCD) method for design development, while the System Usability Scale (SUS) questionnaire is applied for evaluation. After the redesign using the UCD method, there was an improvement, with the average score reaching 80 with a grade scale of B. These changes successfully addressed the main issues related to content completeness and improved promotions to expand reach, which is expected to provide a better user experience. This is anticipated to contribute to an overall improvement in user experience and strengthen the image of Arlang Tour and Travel in the tourism industry.